WORD ORDER IN ENGLISH SIMPLE SENTENCES IN ‘THE SCARLET SAILS’ BY ALEXANDER GRIN WITH REFERENCE TO VIETNAMESE EQUIVALENTS / Nguyễn Tố Nga; NHDKH Dr Nguyễn Thị Thu Hương - Nguyễn, Tố Nga
The reason for writing the research lies in two points. The first one is to find out the word order in simple English sentences in “The Scarlet Sails” by Alexander Grin with reference to Vietnamese equivalents. The second point is to apply the findings of the research to give some suggestions to reading and translating English. The research problem is word order in English simple sentences and its Vietnamese equivalents. The scope of the research is word order in simple sentences used in the novel “The Scarlet Sails”. In this research, the author uses a descriptive approach to a genre of discourse: a novel. Within this domain, qualitative method is chosen as the main method to carry out the research because this study focuses on understanding word order in simple sentences used in a novel. Besides, the author would like to also use quantitative method and staticstical instrument in order to list all of the simple sentences, their frequency. Alexander Grin uses all kinds of sentences in his novel. Among those kinds of sentences, simple sentences is mainly used and has the highest rate of use. Vietnamese sentences is similar to English in the general word order in simple sentences: S +V(+O) +Adv. In Vietnamese, as in English, adverbs are put after the verbs they modify. But in Vietnamese, adjectives are not prefixed with to be and adjectives are positioned after the nouns they modify. From the findings of the research, the author suggests to improve translating skill of Vietnamese students via three measures. The author suggests to learn how English and Vietnamese words are arranged to form meaning. In addition, the author suggests some translating rules.